2010
DOI: 10.1007/s12237-010-9277-2
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-, Salinity-, and Size-Dependent Winter Mortality of Juvenile Blue Crabs (Callinectes sapidus)

Abstract: At midlatitudes within its range, overwintering mortality may play an important role in regulating blue crab (Callinectes sapidus) populations. We conducted a 121-day experiment to estimate winter mortality that used realistic temperature acclimation periods prior to and light levels during experiments. A 2 × 2 × 2 factorial experimental design was used to test for the effects of temperature (3°C, 5°C), salinity (10, 25), and sediment (sediment, no sediment) on the survival of juvenile crabs (14-68-mm carapace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 24 publications
(39 reference statements)
3
35
1
Order By: Relevance
“…A central assumption in this calculation is that all crabs survive the winter. Previously (Bauer and Miller 2010), we demonstrated that survival of juvenile blue crabs is dependent upon temperature, salinity, and size. Crabs were least tolerant of low temperature at low salinity, and survival significantly increased with increasing temperature, salinity, and crab size.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…A central assumption in this calculation is that all crabs survive the winter. Previously (Bauer and Miller 2010), we demonstrated that survival of juvenile blue crabs is dependent upon temperature, salinity, and size. Crabs were least tolerant of low temperature at low salinity, and survival significantly increased with increasing temperature, salinity, and crab size.…”
Section: Introductionmentioning
confidence: 87%
“…Previously in the laboratory, we have quantified interactions among temperature, salinity, size, and sex in regulating overwinter mortality in the blue crab Callinectes sapidus (Bauer and Miller 2010). The blue crab is an important benthic predator and scavenger in estuarine ecosystems (Hines 2007) and serves as a link between the benthic and pelagic communities (Baird and Ulanowicz 1989).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of inconsistencies in the length of the sampling period for each stations of the survey, data from the three tributaries (York, James, and Rappahannock) should be used to create indices (Miller et al 2011). When water temperature falls below ~10°C growth ceases and blue crabs become dormant for the winter, burying into sediments (Brylawski & Miller 2006;Bauer & Miller 2010 region, and depth strata into account and using a geometric mean catch per area swept approach (Bonzek et al 2010).…”
Section: Chesapeake Bay Surveysmentioning
confidence: 99%